2022
DOI: 10.7759/cureus.21921
|View full text |Cite
|
Sign up to set email alerts
|

Workup for Suspected Brugada Syndrome: Two Case Reports for the General Practitioner

Abstract: While a large proportion of ST-segment elevation on EKG is related to myocardial ischemia, the differential diagnosis must include pericarditis, channelopathies, and various genetic conditions. Identifying and working up such abnormalities present a challenge to primary care providers (PCPs). We present two clinical cases of young male patients with ST-segment elevation in anteroseptal leads suspicious for Brugada syndrome and show how to risk stratify and manage them.Our first case presents a 23-year-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Brugada syndrome diagnosis can be challenging, as it often requires a combination of clinical, electrocardiographic, and genetic evaluations [2]. The differential diagnosis for ST-T changes in right precordial leads includes anteroseptal ischemia, right bundle branch block, early repolarization syndrome, arrhythmogenic right ventricular cardiomyopathy, various substance abuse, and electrolyte abnormalities [5][6][7][8]. Structural heart disease must be ruled out in every case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brugada syndrome diagnosis can be challenging, as it often requires a combination of clinical, electrocardiographic, and genetic evaluations [2]. The differential diagnosis for ST-T changes in right precordial leads includes anteroseptal ischemia, right bundle branch block, early repolarization syndrome, arrhythmogenic right ventricular cardiomyopathy, various substance abuse, and electrolyte abnormalities [5][6][7][8]. Structural heart disease must be ruled out in every case.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent EKG showed that the patient had a type I Brugada pattern, considered a more severe condition. The change from type II to type I pattern on EKG highlights the dynamic and evolving nature of Brugada syndrome and the importance of continuous monitoring and assessment [6].…”
Section: Discussionmentioning
confidence: 99%